2022
DOI: 10.1038/s41598-022-17700-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in fluid removal of different open-pore elements for endoscopic negative pressure therapy in the upper gastrointestinal tract

Abstract: Endoscopic negative pressure therapy is an effective treatment strategy for various defects of the gastrointestinal tract. The functional principle is based on an open-pore element, which is placed around a perforated drainage tube and connected to a vacuum source. The resulting open-pore suction device can undergo endoluminal or intracavitary placement. Different open-pore suction devices are used for endoscopic negative pressure therapy of upper gastrointestinal tract defects. Comparative analyses for featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The most important effect of ENPT in the duodenal position is fluid removal as well as the removal of active digestive enzymes. Especially, the OFD is very suitable in fluid removal ( 2 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important effect of ENPT in the duodenal position is fluid removal as well as the removal of active digestive enzymes. Especially, the OFD is very suitable in fluid removal ( 2 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…A device composed of an open-pore material, a perforated drain, and a connected negative pressure source is called an open-pore suction device (OPSD) ( 2 ). Endoscopic negative pressure therapy (ENPT) is also known as endoscopic vacuum therapy or endoscopic vacuum-assisted closure.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopy also allows us to evaluate the size of the leak and the extension of the collection, as well as perform endoscopic debridement of necrotic tissue. To apply internal EVT, a flexible perforated drainage tube loaded with an open-pore element (sponge or compress) is placed endoscopically within the extramural cavity through the fistula and connected to a vacuum source [ 75 ]. With the active aspiration of necrotic debris and pus into the open-pore element, the cavity walls collapse, and the pores of the sponge become gradually saturated, resulting in less effective negative-pressure application.…”
Section: Endoscopic Vacuum Therapy Principlementioning
confidence: 99%
“…The feasibility and efficacy of this treatment have been demonstrated in small case series for various duodenal defects, including perforated duodenal diverticula, iatrogenic perforations after ERCP or endoscopic mucosal resection, and anastomotic leaks, and it has been a game changer for the minimally invasive treatment of these challenging cases [25, 3134]. A recent experimental study also showed the high drainage capacity of the OFD, a feature particularly important in the duodenum, where the presence of bile and pancreatic secretions can have a negative effect on tissue healing [35].…”
Section: Clinical Applications and Outcomes Of Ofdmentioning
confidence: 99%